2011
DOI: 10.1590/s0365-05962011000700044
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de restauração imune associada à histoplasmose

Abstract: Abstract:A 27-year-old HIV-positive male patient with disseminated cutaneous histoplasmosis was treated with both HAART and amphotericin B (total accumulated dose of 0.5g). Amphotericin B was later replaced with itraconazole (200mg/day). Two months after therapy had been started and the cutaneous lesions had healed, the patient interrupted both treatments voluntarily and his health deteriorated. HAART was then re-introduced and CD4+ cell count increased sharply at the same time as lymph node histoplasmosis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Nacher et al 20 described a higher incidence of disseminated histoplasmosis among patients that recently started on antiretroviral therapy, suggesting that this treatment can lead to unmasking IRIS. Passos et al 21 reported the case of paradoxical histoplasmosis IRIS following re-introduction of HAART in a Brazilian patient that voluntarily stopped his HAART and itraconazole prophylaxis. Breton et al 22 presented four patients with HIV-associated with unmasking and paradoxical disseminated histoplasmosis IRIS.…”
Section: Discussionmentioning
confidence: 99%
“…Nacher et al 20 described a higher incidence of disseminated histoplasmosis among patients that recently started on antiretroviral therapy, suggesting that this treatment can lead to unmasking IRIS. Passos et al 21 reported the case of paradoxical histoplasmosis IRIS following re-introduction of HAART in a Brazilian patient that voluntarily stopped his HAART and itraconazole prophylaxis. Breton et al 22 presented four patients with HIV-associated with unmasking and paradoxical disseminated histoplasmosis IRIS.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological observation of few yeasts and abundant inflammatory response in the patient’s second skin biopsy (compared to the findings of abundant yeasts but little inflammation noted on the biopsy at initial presentation), combined with the observed clinical improvement with a regimen that included prednisone, suggest that a paradoxical IRIS (apparent clinical worsening of disease previously controlled upon immune recovery, e.g., ART-mediated CD4+ T-cell lymphocyte repletion) may have contributed to this presentation. Paradoxical IRIS has been reported for other systemic mycoses including cryptococcosis [ 9 ] and occasionally other endemic mycoses like histoplasmosis [ 10 , 11 ] and coccidioidomycosis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases have been described with H. capsulatum var. capsulatum in HIV patients [29,30,31], solid organ transplant recipients [32], and patients receiving TNFα inhibitors [33]. To our knowledge, only one case was described with H. capsulatum var.…”
Section: Fungal-pathogen-associated Iris Characteristicsmentioning
confidence: 99%